Abdul Aziz - Towards a sustainable Open Data Ecosystem: first steps for optimizing findability and user feedback - Aziz, Abdul (Jornada de Jóvenes Investigadores del I3A, 2022)
Towards a sustainable Open Data Ecosystem: first steps for optimizing findability and user feedback